Democracy and alternative modes of governance - Fink-Hafner, Danica (Teorija in praksa, 2017)
While governance literature either analyses particular modes of governance or focuses on case studies, there is a gap in the literature in the longitudinal tendencies of the joint impact of various modes of governance on democracy as regards a particular country. The article provides a framework for analysing types of governance in a post-socialist country in which liberal democracy is being consolidated and at the same time challenged by various modes of post-liberal-democratic governance. The article offers a typology of governance in terms of both the nature of governance (public, private, mixed governance) and the presence or absence of a governing territoriality. It also offers the democratic value dimensions for an evaluation of governance.
Keywords: Democracy; Demokracija; Globalizacija; Globalization; Slovenia; Slovenija; Values; vladavine; Vrednote